2008
DOI: 10.1093/brain/awn331
|View full text |Cite
|
Sign up to set email alerts
|

Powerful beneficial effects of macrophage colony-stimulating factor on  -amyloid deposition and cognitive impairment in Alzheimer's disease

Abstract: Alzheimer's disease is a major cause of dementia in humans. The appearance of cognitive decline is linked to the overproduction of a short peptide called beta-amyloid (Abeta) in both soluble and aggregate forms. Here, we show that injecting macrophage colony-stimulating factor (M-CSF) to Swedish beta-amyloid precursor protein (APP(Swe))/PS1 transgenic mice, a well-documented model for Alzheimer's disease, on a weekly basis prior to the appearance of learning and memory deficits prevented cognitive loss. M-CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
178
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(196 citation statements)
references
References 39 publications
14
178
1
3
Order By: Relevance
“…Senile plaques were smaller, and microglia phagocytosed A␤ in the brain of mice treated with M-CSF. 34 These data indicate that the mechanism of neuroprotection by IL-34 is different from that of M-CSF. Recent reports have demonstrated that IL-34 and M-CSF differ in their structure and the CSF1R domains that they bind, which causes different bioactivities and signal activation kinetics.…”
Section: Discussionmentioning
confidence: 95%
“…Senile plaques were smaller, and microglia phagocytosed A␤ in the brain of mice treated with M-CSF. 34 These data indicate that the mechanism of neuroprotection by IL-34 is different from that of M-CSF. Recent reports have demonstrated that IL-34 and M-CSF differ in their structure and the CSF1R domains that they bind, which causes different bioactivities and signal activation kinetics.…”
Section: Discussionmentioning
confidence: 95%
“…Lee, Jin, Endo et al Some reports have previously shown that microglia are unable to eliminate Ab plaques, release cytotoxic cytokines, and participate in plaque formation as AD progresses [36,37]. However, Boissonneault et al [38] recently reported that M-CSF increases microglial cell number and stimulates Ab degradation. In addition, Ohtaki et al [17] suggested that BM-MSC treatment increases immune responses, including microglia activation and secretion of neuroprotective cytokines in ischemia mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, injecting macrophage colony-stimulating factor (M-CSF) to transgenic mice that spontaneously develop AD on a weekly basis prior to the appearance of learning and memory deficits prevented cognitive loss [4]. The treatment also restored the number of Ly6Chigh (e.g., M1) monocytes in the blood and greatly decreased Aβ levels [5].…”
mentioning
confidence: 99%